Primitive Auxin Response without TIR1 and Aux/IAA in the Charophyte Alga Klebsormidium nitens - Ohtaka, Kinuka (Plant Physiol, 2017)
The phytohormone auxin regulates many aspects of growth and development in land plants, but the origin and evolution of auxin signaling and response mechanisms remain largely unknown. Indeed, it remains to be investigated whether auxin-related pathways diverged before the emergence of land plants. To address this knowledge deficit, we analyzed auxin responses in the charophyte alga Klebsormidium nitens NIES-2285, whose ancestor diverged from a green algal ancestor during the evolution of land plants. This strain is the same as Klebsormidium flaccidum NIES-2285, for which the draft genome was sequenced in 2014, and was taxonomically reclassified as K. nitens. This genome sequence revealed genes involved in auxin responses. Furthermore, the auxin indole-3-acetic acid (IAA) was detected in cultures of K. nitens, but K. nitens lacks the central regulators of the canonical auxin-signaling pathway found in land plants. Exogenous IAA inhibited cell division and cell elongation in K. nitens. Inhibitors of auxin biosynthesis and of polar auxin transport also inhibited cell division and elongation. Moreover, exogenous IAA rapidly induced expression of a LATERAL ORGAN BOUNDARIES-DOMAIN transcription factor. These results suggest that K. nitens has acquired the part of the auxin system that regulates transcription and cell growth without the requirement for the central players that govern auxin signaling in land plants.